TOPVISOR: Two‐level controller‐based approach for service advertisement and discovery in vehicular cloud network. (21st October 2019) - Jafari Kaleibar, Farhoud; Abbaspour, Maghsoud
Summary: Vehicular cloud is a kind of mobile cloud in which vehicles share their resources and provide services for each other. The first step in establishing a vehicular cloud network is the service advertisement and discovery. Due to the dynamic nature of vehicular cloud networks, services are not continuous and the service location may vary at any time depending on the vehicle location. Therefore, higher network traffic is generated to access the consistent and up‐to‐date information. In this paper, a two‐level hierarchical approach is proposed for service advertisement and discovery in vehicular cloud networks. To register the services' specification in this approach, the distributed directories in RSUs and central controllers are used. Moreover, a method is used to avoid extra update packets by localizing the updates. The simulation results show improvement in the packet delivery rate as well as a reduction in transmission bandwidth preventing the network congestion. Abstract : To avoid the network congestion by controlling the update messages, an approach considering the variety of vehicular cloud network services is proposed in this paper. This approach is used to manage the service discovery and advertisement, the provider mobility challenges and scalability issues.